KONFLIK SOSIAL DALAM NOVEL LONTARA RINDU KARYA S. GEGGE MAPPANGEWA - Mahfiroh, Anis Satul; Priyadi, Antonius Totok; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMany novel authors have drawn the meaning of social conflicts. Social conflict is a disagreement between some characters or something outside of himself due to the desire to control, drop and negate each other to meet the needs of individuals and social beings. This qualitative descriptive study aims to describe social conflicts in Lontara Rindu novel by s. Gegge Mappangewa. First is how the form, the cause, how to solve and what of its impact of social conflicts. Moreover, this research also aims to develop readers in understanding about the relationship of author’s life and his creation (literatures). The research instrument is documentation. The research data were phrases, sentences, and quotes, which are related to the research. Technique of data analysis were observing, triangulation and referential. The research result showed there were 31 social conflicts of five kinds of conflicts. Four causing factors were found with five problem solving of social conflicts. The researcher also discovered five kinds of impact of social conflict. The the study results is integrated with the learning of bahasa Indonesin grade XII of SMA equivalent incurriculum 2013 with KD 3.3 analyzing novel texts either through oral and written and KD 4.2 producing novel text which is coherent in accordance with text characteristics both orally and in writing.Keywords: Conflict, Social Conflict, Novel Lontara Rindu